KOMPETENSI PEGAWAI KOMISI PEMILIHAN UMUM KABUPATEN SUMEDANG - Agustin, Irma Dewi (LPPM UNSAP & FISIP UNSAP, 2023)
Good competence comes from qualified human resources. The high and low quality of human resources will also have an impact on the level of productivity and the level of participation in the world of work. To meet organizational expectations, competent human resources are needed. But in addition to achieving goals, the process of achieving those goals is no less important. Therefore, the work done must remain based on values that are in accordance with the organization. This study aims to determine the competence of employees of the Sumedang Regency General Election Commission Office. The targets in this study were 30 employees of the Sumedang Regency General Election Commission Office while the research informants were 3 employees of the Sumedang Regency General Election Commission Office. The sampling technique used to determine research informants used purposive sampling techniques. Data collection was carried out using literature studies and field studies. For data analysis using data reduction, data presentation, and conclusions. The results showed that the competence of employees of the Sumedang Regency General Election Commission Office has met the criteria for employee competency characteristics, but the level of employee competence can be said to be quite good. Employees have understood and fulfilled organizational goals, duties and functions, and standard operating procedures but there are still employees whose confidence level is not high and some employees have not been included in trainings. This causes a lack of employee initiative in the solutions taken to solve the problems faced at work.